Risk factors associated with gestational transient thyrotoxicosis and their effects on the pregnancy course - Bagdagul Yuksel Guler; Ibrahim Demirci; Cem Haymana; Alper Sonmez; Ahmet Faruk Yagci (Archives of Endocrinology and Metabolism)
Abstract Objective: To investigate the clinical characteristics of patients with gestational transient thyrotoxicosis and its possible impacts on pregnancy. Methods: This retrospective study included pregnant women with gestational transient thyrotoxicosis who were admitted to our endocrinology outpatient clinic from June 2020 to March 2023. Patients with other causes of thyrotoxicosis, such as Graves’ disease, toxic nodular goiter, and subacute thyroiditis, were excluded. Results: The study included 50 pregnant women who met the inclusion criteria and whose data could be accessed. Two pregnant women were diagnosed with gestational diabetes, and two pregnancies resulted in abortion. We observed that thyroid-stimulating hormone levels normalized to euthyroid values at a mean gestational age of 18.3 ± 3.7 weeks. The mean gestational age at birth was 38 ± 1.8 weeks. The frequency of preterm labor, defined as delivery before 37 weeks, was 10% (n = 5). Sinus rhythm was observed in 87% of the electrocardiograms obtained during thyrotoxicosis, while sinus tachycardia was detected in four and sinus arrhythmia in two cases. Thyroid nodules were observed in 23 (47.9%) of 48 cases in which ultrasonography was performed during thyrotoxicosis. Discussion: This retrospective study, including 50 pregnant women with gestational transient thyrotoxicosis, found no increase in the rate of serious obstetric complications such as eclampsia/preeclampsia, gestational diabetes, preterm labor, or abortion. Notably, in a detailed examination of electrocardiograms, which has not been done in previous studies, we did not detect any serious, life-threatening arrhythmias, although tachycardia was observed.